2019
DOI: 10.1530/biosciprocs.17.0017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of semen on inflammatory modulators of embryo implantation

Abstract: Insemination transmits to the female reproductive tract constituents of seminal plasma that target uterine epithelial cells to activate a cascade of inflammatory and immunological changes. Experiments in rodents show seminal factor signalling acts to 'condition' the female immune response to tolerate the conceptus, and to organise molecular and cellular changes in the endometrium to facilitate embryo development and implantation. The active factors in seminal plasma are identified as members of the transformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It is well known that under physiological conditions in pigs, AI components, including seminal plasma (SP) and spermatozoa, provoke a rapid uterine inflammatory response that induces changes at the cellular and molecular levels [5][6][7][8]. This immediate endometrial inflammatory reaction post-insemination is transient and quickly gives rise to an anti-inflammatory immunotolerant environment that favors embryo survival and proper progression of pregnancy [8][9][10][11][12]. Additionally, the female reproductive tract is able to detect embryo presence prior to implantation and to accordingly modify its immune response [13,14] towards successful implantation [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that under physiological conditions in pigs, AI components, including seminal plasma (SP) and spermatozoa, provoke a rapid uterine inflammatory response that induces changes at the cellular and molecular levels [5][6][7][8]. This immediate endometrial inflammatory reaction post-insemination is transient and quickly gives rise to an anti-inflammatory immunotolerant environment that favors embryo survival and proper progression of pregnancy [8][9][10][11][12]. Additionally, the female reproductive tract is able to detect embryo presence prior to implantation and to accordingly modify its immune response [13,14] towards successful implantation [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the TGF-β cytokine family plays a major role in the immunomodulatory effects of SP on the maternal genital tract that lead to a preimplantation immunotolerant environment, which is crucial for the establishment of pregnancy [ 56 ]. Moreover, it has been reported that exogenous TGF-β enhances human embryo development in vitro by increasing the number of blastomeres and promoting blastocyst proliferation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that seminal plasma per-se , and in particular the TGFß component of this, are important for the recruitment of leukocytes to the uterus and their involvement in the development of immune tolerance to potential paternal alloantigens expressed by the fetus (Robertson et al, 2006 ; Robertson, 2007 ). Some of these experiments made use of relatively gross manipulations of seminal plasma, for example, mating with animals which had had their seminal vesicles surgically removed (Johansson et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to suggest that during copulation, besides spermatozoa, seminal plasma also delivers a range of signaling molecules into the female tract (Robertson et al, 2006 ; Robertson, 2007 ; Bromfield, 2014 ). One of the most important of these is TGFβ (Sharkey et al, 2012a ), though other molecules, including prostaglandins are likely to be involved.…”
Section: Introductionmentioning
confidence: 99%